Uniting Electroceutical and Cosmeceutical Interventions in Combating Coronavirus Using Ԑ-Poly-l-Lysine - Rania M. Hathout; Dina H. Kassem (MDPI AG, 2020)
Combating the COVID-19 pandemic warrants the exploitation of all the available tools and implies a major focus on both the biological and the physical properties of the causing virus (SARS-CoV2). We hereby introduce a new prophylaxis hypothesis by decreasing the viral load in the body entrances such as the nose and the mouth using pharmaceutical and cosmeceutical preparations that incorporate viral electrostatic repulsive nanofibers fabricated from an abundant marine-derived or a fermentation product polymer; Ԑ-poly-l-lysine was prepared using the electrospinning technique.